iTRACK Technologies feasibility study of an RFID system service provider in the Philippines - Arguelles, Claire Christine; Hamdain, Khalil; Malaki, Ann; Principe, Rodellon
iTRACK Technologies is a corporation providing RFID solutions for tracking, asset management and data management needs. iTRACK's main product is OmniTag, a versatile RFID system in the form of an RFID reader imbedded in a PC host. iTRACK aims to become the pioneer and premiere local RFID solutions provider offering high quality products custom fitted to its client's needs. The company shall start-up with 3 prong management backed up by a set of Board of Directors and the Stockholders. Market Analysis defined NCR and Region IVA as comprising 39.55% of the Philippines' manufacturing, retail, financial, utilities and transportation industries-iTRACK's chosen target market. Demand projections for OmniTag are at a conservative 1872 units annually shall, which translates to approximately 156 units per month. iTRACK sees supermarkets as its primary customers as these have a greater need for item level tracking-a feat pioneered by Wal-mart 5 years ago when it mandated its suppliers to use RFID when providing supplies to its warehouses as part of their inventory tracking initiatives. There are no local providers of RFID systems in the Philippines, much less those who offer RFID solutions. It may be said that the manual system, especially the barcode are among the RFID system's close contenders in spite the fact that the RFID remains unparalleled when it comes to information provided on a single tag. Globally, Alien Technologies and Motorola had been the top RFID solutions providers when it comes to innovation, service and market penetration. As a local RFID solutions provider, iTRACK has the advantage of working within close proximity to its target market. It shall operate both as an assembler and provider of value added services of customized applications crafted to fit a client's tracking needs. All components will be outsourced from local providers except for the SkyeTek reader exclusively manufactured by Skyetek in Colorado. Location, production, facilities and manpower were evaluated to come up with alternatives that support the marketing plan. Given that the market targets are met, the company is looking at Php 51.3 Million income after taxes during in its first year of operation to as much as Php 58.7 Million at year 5. While it is true that barcodes will be around for the next 15 years, the increasing globalization coupled with fast and information intensive operations may prove investments on RFID systems worthwhile.